Some morphological and anatomical studies of leaves and flowers of Murraya paniculata (Jack) Linn. in vivo and in vitro - Taha, R.M.; Haron, N.W. (2008)
In the present study, various explants of Murraya paniculata (Jack) Linn., such as cotyledons, shoots and young stems were cultured on MS medium supplemented with various concentrations of Benzyl Amino Purine (BAP) under 25±1°C with 16 h light and 8 h dark and also 8 h light and 16 h dark to obtain complete plant regeneration. In vitro flowering was observed from shoot explants cultured on MS supplemented with 0.5-2.0 mg L-1 Naphthalene Acetic Acid (NAA) and also on MS basal medium under similar conditions. The leaves and flowers obtained from both in vivo and in vitro conditions were examined and compared. Morphological studies such as leaf clearing, epidermal peeling were studied using light and scanning electron microscope. Macromorphological studies of the flowers produced from in vivo and in vitro conditions were also examined. Morphologically, there were no differences between in vivo and in vitro flowers except the flowers produced from tissue culture systems were smaller in size with protruding stigmas. Differences were also found in the number of layers of palisade cells and the presence or absence of epicuticle layer of the leaves. Leaves produced from tissue culture system were smaller in size with membranous texture. Stomata were present only on the abaxial surfaces of both in vivo and in vitro leaves but the stomata were raised above the epidermis in the latter. © 2008 Asian Network for Scientific Information.